1997
DOI: 10.1038/eye.1997.131
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ocular pulse amplitude in low tension glaucoma is independent of vasospasm

Abstract: Methods: OPA, using the Langham Ocular Blood Flow (OBF) System, applanation intraocular pressure (lOP), systemic blood pressure and heart rate were measured and vasospasm was determined by a fingernail capillary blood flow test.Results: OPA (mmHg) in the LTG patients with a vasospastic reaction (LTG-V, 1.4 ± 0.1, n = 17) was not significantly (p>0.09) different when compared with non-vasospastic LTG patients (LTG-NV, 1.5 ± 0.2, n = 15) but was significantly (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 20 publications
4
17
0
7
Order By: Relevance
“…The OPA has been used in many studies as an indirect measure of the choroidal perfusion [6,[15][16][17]. Differences in IOP values during systole and diastole are used to calculate an index that estimates ocular blood supply, whereas about 70-80% of it is due to the choroidal flow [6].…”
Section: Discussionmentioning
confidence: 99%
“…The OPA has been used in many studies as an indirect measure of the choroidal perfusion [6,[15][16][17]. Differences in IOP values during systole and diastole are used to calculate an index that estimates ocular blood supply, whereas about 70-80% of it is due to the choroidal flow [6].…”
Section: Discussionmentioning
confidence: 99%
“…This IOP pulse wave has been used as a means of assessing the ocular vascular status in glaucoma patients. Numerous studies have demonstrated reduced IOP pulse amplitudes and reduced pulsatile ocular blood flow in glaucoma patients compared with control subjects [11,14,15,20,21,22,24].…”
Section: Introductionmentioning
confidence: 98%
“…Während Patienten mit primärem Offenwinkelglaukom ein chronisch-erhöhtes intraokulares Druckniveau aufweisen, gibt es Patienten, die ohne eine Erhöhung des IOD, sowohl funktionell als auch morphologisch, alle Symptome eines Glaukomschadens aufweisen [12]. Als Ursache dieses so genannten Normaldruckglaukoms (NDG) wird eine Störung der okulären Perfusion angenommen [26], da für Patienten mit NDG bekannt ist, dass diese signifikant häufiger an vaskulären Erkrankungen wie Migräne und Vasospasmen leiden [4,21].…”
Section: Introductionunclassified